Beyond force generation: Why is a dynamic ring of FtsZ polymers essential for bacterial cytokinesis?. (7th November 2016) - Coltharp, Carla; Xiao, Jie
Abstract : We propose that the essential function of the most highly conserved protein in bacterial cytokinesis, FtsZ, is not to generate a mechanical force to drive cell division. Rather, we suggest that FtsZ acts as a signal‐processing hub to coordinate cell wall synthesis at the division septum with a diverse array of cellular processes, ensuring that the cell divides smoothly at the correct time and place, and with the correct septum morphology. Here, we explore how the polymerization properties of FtsZ, which have been widely attributed to force generation, can also be advantageous in this signal processing role. We suggest mechanisms by which FtsZ senses and integrates both mechanical and biochemical signals, and conclude by proposing experiments to investigate how FtsZ contributes to the remarkable spatial and temporal precision of bacterial cytokinesis. Abstract : FtsZ polymers form a dynamic, discontinuous ring that is critical for bacterial cytokinesis. Here, we propose that these polymers perform a signaling function rather than a force‐generating function. We describe how signaling from FtsZ can ultimately modulate cell wall synthesis, which is the more likely driving force in bacterial cytokinesis.